2021
DOI: 10.1097/gox.0000000000003849
|View full text |Cite
|
Sign up to set email alerts
|

Do Dedicated Research Years during Medical School Predict Academic Productivity during Residency?

Abstract: Background: Evidence regarding whether medical school research portends resident research is limited. This information will provide program directors with data that may be useful for selecting applicants with a commitment to continued academic productivity. Methods: A questionnaire distributed via the American Society of Plastic Surgeons Resident Council to residents in 44 plastic surgery training programs in May 2020 assessed participation in dedicated research years during medical school, the number of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…These data suggest that a history of academic projects may be predictive of future academic productivity. These results are well aligned with prior studies conducted in other specialties, including otolaryngology, pediatrics, dermatology, neurology, urology, plastic surgery, and radiology . Medical students who successfully published early in their career may garner experience and skills performing research, which can be leveraged during residency and into their career as responsibilities and workload continue to grow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that a history of academic projects may be predictive of future academic productivity. These results are well aligned with prior studies conducted in other specialties, including otolaryngology, pediatrics, dermatology, neurology, urology, plastic surgery, and radiology . Medical students who successfully published early in their career may garner experience and skills performing research, which can be leveraged during residency and into their career as responsibilities and workload continue to grow.…”
Section: Discussionmentioning
confidence: 99%
“…These results are well aligned with prior studies conducted in other specialties, including otolaryngology, pediatrics, dermatology, neurology, urology, plastic surgery, and radiology. [7][8][9][14][15][16][17] Medical students who successfully published early in their career may garner experience and skills performing research, which can be leveraged during residency and into their career as responsibilities and workload continue to grow. Parker et al 18 demonstrated that participation in an organized research program is associated with the pursuit of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses across various specialties outside of radiation oncology have demonstrated that prior research productivity may predict research productivity during residency. 8 , 9 , 10 However, this question has not yet been explored in the context of radiation oncology, despite its emphasis on research. Thus, this study aimed to determine whether research productivity before residency (ie, during medical school) could predict future research productivity during radiation oncology residency.…”
Section: Introductionmentioning
confidence: 99%
“…11,[18][19][20][21] Moreover, few of these objective application components have significant utility as indicators for applicant competitiveness or future achievement. 22,23 Although subjective metrics including letters of recommendation and research productivity may offer greater insight on future success, 24,25 access to quality mentorship, research funding, substantive academic opportunities, and other implicit necessities for a competitive application are not universally accessible. 15,26 Socioeconomic disparities among medical students, PRS programs, and academic institutions disproportionately burden marginalized applicants, perpetuating pipeline issues.…”
mentioning
confidence: 99%